Reconciliation(s) : transitional justice in postconflict societie s (Montreal ; Ithaca [N.Y.] : McGill-Queen's University Press, 2009)
'Reconciliation(s)' considers the definition of the concept of recon ciliation itself, focusing on the definitional dialogue that arises fro m the attempts to situate reconciliation within a theoretical and analy tical framework.
Introduction / Joanna R. Quinn -- Forgiveness as righteousness / Laurence Thomas -- Towards the healing of history: an explorat ion of the relation between pardon and peace / Nicholas Frayling -- Dialectic of acknowledgment / Trudy Govier -- Transitional ju stice in Morocco: lifting the veil on a hidden face / Veerle Opgenha ffen and Mark Freeman -- Traditional justice and legal pluralism in transitional context: The case of Rwanda's Gacaca Courts / Rosemary Nagy -- Truth and the challenge of reconciliation in Guatemala / Anita Isaacs -- Contact and culture: mechanisms of reconciliation in schools of North Ireland and Israel / Caitlin Donnelly and Joanne H ughes -- What reconciliation? Traditional mechanisms of acknowledgme nt in Uganda / Joanne R. Quinn -- Survey of reconciliation proces ses in Bosnia and Herzegovina : the gap between people and politics / Valery Perry -- Tensions between human rights and the politics o f reconciliation : a South African case study / Stephanus Du Toit -- Interethnic reconciliation in Lebanon: after the Civil War / Sam ar El-Masri -- Beyond coexistence: Towards a working definition of r econciliation / Brandon Hamber and Grâainne Kelly.
Includes bibliographical references and index.
Keywords: Reconciliation -- Political aspects; Justice, Administration of; Restorative justice; Transitional justice; Human rights; Crimes against humanity; Peace-building.